Assertive Speech Acts between Telecommunication Call Center with Customers: Study of Pragmatic (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The objective of this research is to describe the use of Assertive Speech acts form, which contained in a conversation between call center Telkom wit customers. In the other hand, this research also describes the study of pragmatic into indirect speech conversation. This research is descriptive qualitative research. The data was collected by a recorded method, noted technique, a free and involved technique (SBLC). Analysis contextual technique and analysis heuristic technique is used as the data analysis on this research. The data resource that took is the speech act of call center Telkom with the customers were recorded by phone and live chat, on a piece of speech between call center Telkom with the customers. The subject of this research is the assertive speech acts between call center Telkom with the customers in the study of pragmatic. The results of this research are in the form of assertive speech acts, the function o assertive speech acts, and the cause factor of assertive speech acts used in a conversation between call center Telkom with customers. The assertive speech acts that found in a conversation between call center Telkom with customers are the speech of propose, brag, mention, and report.